Keep Safe: collaborative practice development and research with people with learning disabilities. Issue 4 (4th December 2020) - Wake, Anthony; Davies, Jill; Drake, Celia; Rowbotham, Michael; Smith, Nicola; Rossiter, Rowena
Abstract : Purpose: This collaborative paper (working together) describes collaborative practice development and research by and with people from the learning disabilities community. This paper aims to show some of the activities which supported the collaborative practice development and research to show and encourage others to do more collaboration. The paper format is based on a previous collaborative paper published in the Tizard Learning Disability Review (Chapman et al., 2013). Design/methodology/approach: The collaborative practice development and feasibility study [1 ] focuses on an intervention called Keep Safe. This is an intervention for young people with learning disabilities who are 12 years and older and have shown "out-of-control" or harmful sexual behaviour. Findings: The paper gives examples of activities of the Keep Safe Advisory Group in planning, doing and thinking about Keep Safe development and feasibility. The authors list some good things and some difficulties in collaborating. They look at which parts of Frankena et al.'s (2019a) Consensus Statement on how to do inclusive research were done, which ones were not, and why. Social implications: The paper ends with some thoughts about collaborating with people from the learning disabilities community: for people with learning disabilities, practitioners and researchers. Originality/value: The paper is original in its illustration of collaborative practice development and research and measuring the activities against the inclusive research consensus statement.